Clinical practice guideline for the evaluation and management of upper gastrointestinal bleeding in EsSalud: 2024 Update - Cervera-Caballero, Luis (2025)
Introduction: This article summarizes the clinical practice guideline (CPG) for the evaluation and management of upper gastrointestinal bleeding (UGIB) in the Social Security of Peru (EsSalud). Methods: A guideline development group comprising medical specialists and methodologists, formulated clinical questions addressed by CPG. Systematic evidence searches were conducted for each question during 2024. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology was used to assess the certainty of the evidence and formulate the recommendations. The CPG was approved through Resolution No. 000022–IETSI-ESSALUD-2024. Results: This CPG addressed 11 clinical questions, divided into four topics: risk assessment, initial management, variceal UGIB management, and non-variceal UGIB management. Based on these questions, 11 recommendations (7 strong recommendations and 4 weak recommendations), 24 good clinical practices, and 2 flowcharts were formulated. For the 2024 guideline update, no new evidence was found to change the recommendations' direction or strength. Conclusion: This article summarizes the methodology and evidence-based conclusions from the CPG for evaluating and managing UGIB in EsSalud.